Traumatic pediatric shoulder fracture-dislocation in a 14-year-old child - Meryem Fettah; Imane Oualili; Mohamed Mimouni; Hatim Jabri; Mohamed Tazi charki; Hicham Abdellaoui; Karima Atarraf; Moulay abderahmane Afifi (Elsevier, 2022)
Proximal humerus fractures is often encountered in pediatric traumatology, while scapulohumeral dislocation is rare, and its association with the fracture of the proximal humerus is exceptional. This makes its management subject to discussion.We report the case of a fracture of the upper end of the humerus associated with scapulohumeral dislocation in a 14-year-old child, the victim of shoulder trauma with direct shock, treated by open-air reduction.